Methane emission and rice growth on clayey soil under controlled water regime - Kaharuddin Kaharuddin; Sikstus Gusli; Muh Jayadi; Amirullah Dachlan; Andi Muh. Ilham (Future Science, 2022)
Conventional lowland rice cultivation involves flooding the paddy from planting to close to harvest, and high N fertilization. This practice leads to large amount of methane emissions. We studied the effect of soil water regime control on methane gas emissions and growth of several rice varieties on clayey soil. The experiment was arranged according to Split Plot Design. The main plot was water regime, i.e. continuous flooding (2-cm inundation), and intermittent flooding (flooded 2 cm then allowed to dry until the soil started to cracks). The sub-plots consisted of 3 rice varieties, i.e. Inpari 32, Mekongga, and Cisadane. Together, there were six treatment combinations, repeated 4 times. We measured methane emission, plant height, number of tillers per clump, number of productive tillers, and root volume. We computed analysis of variance, then performed Duncan Multiple Range Test. We found, at 57 and 73 days after planting, continuous flooding resulted in much (statistically) higher methane gas emissions than intermittent flooding (about 2 times greater for both Inpari and Cisadane, and 5 times greater for Mekongga). The two water regimes examined did not result in differences in plant height, number of tillers, productive tillers and root volume of the three varieties, although the flooded treatment tended to slightly give taller plant, more tillers and productive tillers. In conclusion, intermittent flooding significantly suppresses methane emission compared to continuous flooding. However, certain rice variety produces more methane than others. While intermittent flooding reduced methane emission, it did not statistically affect rice growth compared to continuous flooding.